2012
DOI: 10.5505/1304.7361.2012.55823
|View full text |Cite
|
Sign up to set email alerts
|

Patient and relative complaints in a hospital emergency department: a 4-year analysis

Abstract: ÖZET Amaç Hasta ve yakınlarının şikâyetleri, hizmet iyileştirmeleri için önemli bir bilgi kaynağıdır. Bu çalışmada; düzeltici önlemler almak amacıyla, hasta ve yakınlarının acil servis hakkında şikâyetleri değerlendirildi. Gereç ve Yöntem SUMMARY ObjectivesComplaints by patients and their relatives are an important source of information for service improvement. In order to take remedial measures, the present study evaluated the complaints of patients and their relatives about our emergency department (ED). Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 7 publications
2
9
0
1
Order By: Relevance
“…Usually more than 50% of complaints are presented by patients' relatives. In studies conducted in England, Singapore, Turkey and Iran (Tehran) this number ranged from 50-86% (10,15,16). This might be because of the patients' health status which does not usually allow them to report and pursue their complaints.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Usually more than 50% of complaints are presented by patients' relatives. In studies conducted in England, Singapore, Turkey and Iran (Tehran) this number ranged from 50-86% (10,15,16). This might be because of the patients' health status which does not usually allow them to report and pursue their complaints.…”
Section: Discussionmentioning
confidence: 99%
“…Montini et al in Boston showed that communication failure was also the second cause of complaints (2); while in Italy, Victoria and Singapore as well as Turkey this issue was accounted for most of complaints (2,(9)(10)(11)15,16,23). Improper communication or providing incomplete or inappropriate explanations are usually the consequences of patients' dissatisfaction with personnel behavior.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations